Methylene Blue Administration During and After Life-Threatening Intoxication by Hydrogen Sulfide: Efficacy Studies in Adult Sheep and Mechanisms of Action. (24th December 2018) - Haouzi, Philippe; Tubbs, Nicole; Cheung, Joseph; Judenherc-Haouzi, Annick
Abstract: Exposure to toxic levels of hydrogen sulfide (H2 S) produces an acute cardiac depression that can be rapidly fatal. We sought to characterize the time course of the cardiac effects produced by the toxicity of H2 S in sheep, a human sized mammal, and to describe the in vivo and in vitro antidotal properties of methylene blue (MB), which has shown efficacy in sulfide intoxicated rats. Infusing NaHS (720 mg) in anesthetized adult sheep produced a rapid dilation of the left ventricular with a decrease in contractility, which was lethal within about 10 min by pulseless electrical activity. MB (7 mg/kg), administered during sulfide exposure, maintained cardiac contractility and allowed all of the treated animals to recover. At a dose of 350 mg NaHS, we were able to produce an intoxication, which led to a persistent decrease in ventricular function for at least 1 h in nontreated animals. Administration of MB, 3 or 30 min after the end of exposure, whereas all free H2 S had already vanished, restored cardiac contractility and the pyruvate/lactate (P/L) ratio. We found that MB exerts its antidotal effects through at least 4 different mechanisms: (1) a direct oxidation of free sulfide; (2) an increase in the pool of "trapped" H2 S in red cells; (3) a restoration of the mitochondrial substrate-level phosphorylation; and (4) a rescue of the mitochondrial electron chain. In conclusion, H2 S intoxication produces acute and long persisting alteration in cardiac function in large mammals even after all free H2 S has vanished. MB exerts its antidotal effects against life-threatening sulfide intoxication via multifarious properties, some of them unrelated to any direct interaction with free H2 S.